Asymptotic Dynamics and Spectral Analysis for Schrödinger Operator with Weakly Accelerated Potential. (2015) - Jelić, Gordana
Abstract: The main result of this paper is that, under conditions met by the potential υ, which are there are wave operators The operators W± are unitary and realize the similarity between and H, i.e. H W± = W± . It has been proven that if υ1 and υ2 are two potentials to which the operators H1 and H2 correspond, then there are the wave operators associated with W1, ±, W2, ± by the relations where, .